Mono- And Tripodal Porphyrins: Investigation on the Influence of the Number of Pyrene Anchors in Carbon Nanotube and Graphene Hybrids - Garrido, Marina; Volland, Michel; Münich, Peter Wilhelm; Rodríguez-Pérez, Laura; Calbo, Joaquín; Ortí, Enrique; Herranz, M. ángeles; Martín, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
A series of molecular precursors, containing one (1 and 3) or three (2 and 4) pyrene anchors, covalently linked to porphyrins (free base or Zn), were prepared and characterized. All of them enable their π-πstacking onto low-dimensional nanocarbons including single-walled carbon nanotubes (SWCNTs) and nanographene (NG), their individualization, and their characterization. Microscopic (TEM, AFM) and spectroscopic (steady-state UV-vis and fluorescence, spectroelectrochemistry, and transient absorption measurements) techniques were at the forefront of the characterizations and were complemented by Raman spectroscopy and theoretical calculations. Of great importance is the Raman analysis, which corroborated n-doping of the nanocarbons due to the interactions with 1-4 when probed in the solid state. In solution, the situation is, however, quite different. Efficient charge separation was only observed for the graphene-based system NG/3.
CRIS-Team Scopus Importer:2020-02-04